Empirical analysis on threats to Hong Kong port in regional competitive environment. (24th May 2011) - Tian, Xin; Liu, Li-Ming; Cheng, Si-Wei; Shi, Jianming
Hong Kong and Shenzhen ports share the same hinterland for container cargoes. The overall container volume to and from this hinterland has grew tremendously over the last two decades. At the same time, the market shares of the two ports have been changing dramatically, especially in the last 10 years, with Shenzhen port quickly rising from a negligible local port to a world-class 'equal' player. Will this trend in market share allocation continue? Will market equilibrium be reached eventually? What will be the future for Hong Kong port? To answer these questions, we need to first understand the true competitive relation between the two ports. Using the container throughput data, we show the evolving competition relationship between the two ports and in-coming threats to Hong Kong port empirically. Our empirical evidences complement the theoretical analysis in the literature.